Oleocanthal and oleacein contribute to the in vitro therapeutic potential of extra virgin oil-derived extracts in non-melanoma skin cancer. (October 2018) - Polini, Beatrice; Digiacomo, Maria; Carpi, Sara; Bertini, Simone; Gado, Francesca; Saccomanni, Giuseppe; Macchia, Marco; Nieri, Paola; Manera, Clementina; Fogli, Stefano
Abstract: Although the anticancer properties of extra virgin olive oil (EVOO) extracts have been recognized, the role of single compounds in non-melanoma skin cancer is still unknown. The in vitro chemopreventive and anticancer action of EVOO extracts and oil-derived compounds in non-melanoma skin cancer models were evaluated on cutaneous squamous cell carcinoma cells and on immortalized human keratinocytes stimulated with epidermal growth factor. Preparation of EVOO extracts and isolation of single compounds was carried out by chromatographic methods. Antitumor activity was assessed by cell-based assays (cell viability, migration, clonogenicity, and spheroid formation) and apoptosis documented by internucleosomal DNA fragmentation. Finally, inhibition of key oncogenic signaling nodes involved in the progression from actinic keratosis to cutaneous squamous cell carcinoma was studied by western blot. EVOO extracts reduced non-melanoma skin cancer cell viability and migration, prevented colony and spheroid formation, and inhibited proliferation of atypical keratinocytes stimulated with epidermal growth factor. Such a pharmacological activity was promoted by oleocanthal and oleacein through the inhibition of Erk and Akt phosphorylation and the suppression of B-Raf expression, whereas tyrosol and hydroxytyrosol did not have effect. The current study provides in vitro evidence for new potential clinical applications of EVOO extracts and/or single oil-derived compounds in the prevention and treatment of non-melanoma skin cancers. Highlights: Extra virgin olive oil (EVOO) extracts exert anticancer activity on squamous cell carcinoma. EVOO extracts prevent proliferation of atypical human keratinocytes stimulated with EGF. EVOO extracts reduce protein expression of B-Raf and phosphorylation of Erk 1/2 and Akt. Oleocanthal and oleacein contribute to the anticancer effects by phytoextracts.